Artistic creation as a path to immersion in literature: on the example of excerpts from texts with the theme of the Shoah - Milan Mašát (Cogent Arts & Humanities)
In this article, I present current methods which, in the context of the current knowledge of the didactics of literature, are supposed to lead readers to the text itself and which, in a certain way, through their own artistic (literary) creation, are supposed to introduce them to the issue of literature. The core of the article is the presentation of three excerpts with the theme of the Shoah and the methods of working with them, which were postulated in the intentions of creative activities (literary expressivity). Through a narrative analysis, in this article I answer the following questions: How can texts with Shoah themes be handled in the light of current knowledge of the didactics of literature, and 2. Are excerpts from selected publications suitable for introducing pupils to literary representations of the Shoah? I believe that I have succeeded in demonstrating that texts with relevant themes can be handled in full accordance with the current theses of didactics literature, with the proviso that they are developed by the reader holistically, that is, not only in literary-theoretical concepts, but also in personality traits.